2010
DOI: 10.1016/j.nlm.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and ERβ agonists enhance recognition memory, and DPN, an ERβ agonist, alters brain monoamines

Abstract: Effects of estradiol benzoate (EB), ERα-selective agonist, propyl pyrazole triol (PPT) and ERβ-selective agonists, diarylpropionitrile (DPN) and Compound 19 (C-19) on memory were investigated in OVX rats using object recognition (OR) and placement (OP) memory tasks. Treatments were acute (behavior 4 h later) or sub chronic (daily injections for 2 days with behavior 48 h later). Objects were explored in sample trials (T1), and discrimination between sample (old) and new object/location in recognition trials (T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 74 publications
7
135
2
Order By: Relevance
“…While the effect of estradiol on false memories has not yet been directly examined in humans, recent animal studies have demonstrated improved object recognition memory in rats following estradiol treatment (e.g. Frye et al, 2007;Inagaki et al, 2010;Jacome et al, 2010). In contrast to previous studies investigating recognition performance, the present findings suggest that estradiol does not improve false recognition in humans in general.…”
Section: Estradiol Reduces False Recognition In Highly Schizotypal Wocontrasting
confidence: 99%
“…While the effect of estradiol on false memories has not yet been directly examined in humans, recent animal studies have demonstrated improved object recognition memory in rats following estradiol treatment (e.g. Frye et al, 2007;Inagaki et al, 2010;Jacome et al, 2010). In contrast to previous studies investigating recognition performance, the present findings suggest that estradiol does not improve false recognition in humans in general.…”
Section: Estradiol Reduces False Recognition In Highly Schizotypal Wocontrasting
confidence: 99%
“…Our previous work demonstrated that long-term treatment with E increases NE in the CA3 region of the hippocampus [49]. We have evidence to suggest that the commercially available ER␤ agonist diarylpropionitrile (DPN) also affects noradrenergic parameters in different regions of the hippocampus [50]. The present findings extend these observations by demonstrating Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The fact that the ER␤ ligand had no effect on uterine or body weight but affected levels of neurotransmitters supports the idea that the dose was sufficient to selectively activate the ER␤. In addition, we have recent data to suggest that C19 improves performance in specific memory tasks similar to the ER␤ agonist, DPN [50]. Importantly, the data reflect only one time point and, as mentioned previously, at least some of the effects of E on monoamines are time-dependent [52].…”
Section: Specificity Of Subtype-selective Er Ligandsmentioning
confidence: 51%
“…This suggests that at least some of the effects of estradiol on cognition and behavior may be mediated by ER␤, and recent data point to a crucial role of ER␤ in estrogen-induced learning and memory. In fact, learning ability of ovariectomized ER␤-KO mice was impaired compared to that of WT ovariectomized females, strongly suggesting that ER␤ is required for optimal spatial learning [49,50]. Other studies focussed on anxiety-related behavior.…”
Section: Resultsmentioning
confidence: 99%